First record and revised description of Herpetocypris helenae G. W. Müller, 1908 (Crustacea, Ostracoda) from the Neotropics (central-west Argentina) - D'ambrosio, Débora Sabina (2016)
The genus Herpetocypris Brady & Norman, 1889 has a wide distribution in most of the zoogeographical regions except in the Neotropical Region, where only three species have so far been found these being H. reptans (Baird, 1835), H. chevreuxi (Sars, 1895) and H. pectinata Brehm, 1934. We here report the first record of Herpetocypris helenae G. W. Müller, 1908 from the Neotropical Region, and provide a complete revised description and illustration of the valves and soft parts of this species, as well as information on ecological factors affecting its distribution and aspects of morphological variability of its valves.